Astragaloside IV attenuates high-glucose-Induced peritoneal fibrosis via modulation of the ENKUR/PI3K/Akt signalling pathway - Tianxin Jiang; Lijie Zhang; Jiahan Liu; Xinxin Xu; Yuanyuan Shi; Zhanzheng Zhao; Jing Xiao (PLoS ONE, 2026)
This study aimed to explore the mechanisms by which Astragaloside IV (AS-IV), a major bioactive component of Astragalus membranaceus , mitigates high-glucose-induced peritoneal fibrosis (PF) in peritoneal dialysis (PD). Using both in vivo (uremic rat model) and in vitro (human peritoneal mesothelial cells) approaches, we observed that AS-IV treatment was associated with a significant attenuation of PF. This effect was mediated through the inhibition of epithelial-mesenchymal transition (EMT) and fibrosis. In vivo, AS-IV reduced extracellular matrix deposition and collagen accumulation, downregulated EMT and fibrosis markers (α-SMA, collagen IV), and restored E-cadherin levels. Notably, these changes correlated with the downregulation of ENKUR, pPI3K, and pAkt. The in vitro results corroborated these findings, showing that AS-IV suppressed EMT without cytotoxic effects. Our data indicate that AS-IV may exert antifibrotic effects via modulation of the ENKUR/PI3K/Akt signaling pathway, suggesting a potential target for the prevention of PF.